28 Bioresorbable vascular scaffolds – a tale of two-hundred and fifteen scaffolds from a single centre review. (October 2018) - McInerney, A; McFadden, E
Abstract : Introduction: Bioresorbable vascular scaffolds (BVS) held great promise of overcoming the shortfalls of metallic stents. Significant concerns regarding device thrombosis has quelled this enthusiasm. Some observers have linked this complication to implantation technique. In our institution, bioresorbable vascular scaffolds were predominantly deployed by a single operator in a uniform manner. We reviewed patients who received bioresorbable vascular scaffolds to ascertain our complication rate. Methods: A retrospective review of the case notes of all patients receiving BVS in Cork University Hospital since the date of first to last stent use (October 2013 to March 2017). Demographic, procedural and follow up data was collated. Results: Between October 2013 and March 2017, 249 BVS were deployed in 154 patients giving an average of 1.6 scaffolds per patient. Follow up data was available on 215 scaffolds (86.4%) deployed in 127 patients (average 1.7 scaffolds per patient, range 1–5). One-hundred (79%) were male. The average age was 58 years (±10). The indication was STEMI 50 patients (39.5%), NSTEMI 37 patients (29%), unstable angina 24 patients (18.9%), stable angina or silent ischaemia 16 patients (12.6%). A single operator was responsible for >99% of procedures. Access was via the radial artery for 104 (48%)of the scaffolds deployed and femoral for the remaining 111 (52%) scaffolds. Of the 215 scaffolds, 107 were to the LAD, 38 to the left circumflex, 64 to the right coronray artery, one to a ramus intermedius, one to a diagonal, 2 to an obtuse marginal, and 2 to vein grafts. All lesions were predilated prior to deployment of the BVS. The median scaffold diameter used was 3.5 mm. Half of all scaffolds were deployed with imaging guideance: 85 with OCT and 22 with IVUS. Ninety-six percent were post dilated. The median post dilation pressure was 20 atmospheres. Two patients were found to have inadequate aposition of stent struts despite high post dilation inflation pressures on OCT and both had deployment of metallic drug eluting stents inside the BVS at the index procedure. One patient had a dissection into the LMS and also received metallic DES. All patients received dual antiplatelets. The average duration of follow up was 587 days (range 1–1448). One in-hospital death occurred. No evidence of stent thrombosis was found at post mortem. Two (1.5%) patients had unplanned target lesion revascularisation (TLR). One had an acute stent thrombosis 4 days after his initial stenting procedure requiring primary baloon angioplasty. This occurred in the context of non compliance with dual antiplatelets. The second had angina and severe in stent restenosis requiring depolyment of metallic drug eluting stents. These subsequently also became stenosed ultimately requiring coronary artery bypass grafting. One patient had a repeat coronary angiogram at 18 months and was found to have a focal aneurysmal segment inside the BVS and was prescribed prolonged antiplatelet therapy. Discussion: Despite initial promise the increased rates of stent thrombosis found in several studies has raised concern such that the use of bioresorbable scaffolds has gone into rapid decline. Rates of up to 2.1% at 6 month follow up have been reported. In our study, one patient experienced a stent thrombosis at 4 days post index procedure representing a rate of 0.78% over an average of 19 months of follow up. This occurred in the context of non-compliance with antiplatelet therapy. A high rate of pre and post dilation as well as high rates of intravascular imaging guided deployment and optomisation may explain our low rates of stent thrombosis. Conclusion: Further study is required to ascertain the cause of increased stent thrombosis with the use of bioresorbable scaffolds. Our study suggests that meticulous pre and post dilation with the use of intravascular imaging may decrease the risk of this complication.